The translation and validation of the smartphone use questionnaire (SUQ) into the Malay language - Amirul Danial A,; Suzaily Wahab,; Muhamad Afiq Z,; Rizal AM,; Mohammad Faidzul Nasrudin,; Mohd Juzaiddin Ab A,; Noor Alaudin Abdul Wahab, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Interruptions caused by frequent smartphone use steals attention away from daily activities, bringing serious implications onto an individual’s health, safety and education. Smartphone Use Questionnaire (SUQ) is a 20-item questionnaire developed to assess the pattern of smartphone use and its effect on attention. This study was done to translate and validate the Malay-language version of the SUQ and to measure the psychometric properties of the Malay-version SUQ to justify its use in Malaysia. A forward and back-translation was done by four individuals, who were three physicians and one linguist. Content and face validity was done involving three experts who were a linguist, psychiatrist and epidemiologist. Psychometric testing was conducted on a sample of 195 individuals proficient in the Malay language. A construct validity test was performed using factor analysis and the internal reliability was tested by calculating for the Cronbach’s Alpha. The age range of the sample was 13-59 years, most of which were female and of the Malay race. Using principal component analysis with direct oblimin rotation, the factor analysis extracted two components similar to the original study: General Use and Absent-Minded Use. However, question number 20 was grouped into General Use component, whereas in the original study it was under the Absent-Minded Use component. The Cronbach’s Alpha for the obtained components was 0.884 and 0.927, respectively. This study found that the Malay-version SUQ was a valid and reliable instrument for use in Malaysia in assessing inattention associated with smartphone use.